Src family kinases Fyn and Lyn are constitutively activated and mediate plasmacytoid dendritic cell responses - S. Dallari; M. Macal; M. E. Loureiro; Y. Jo; L. Swanson; C. Hesser; P. Ghosh; E. I. Zuniga (Nature Communications, 2017)
Type I interferon responses are a core immunoregulatory function of plasmacytoid dendritic cells (pDCs). Here the authors show that SFK family members, including Lyn and Fyn, control type I interferon production in human and mouse pDCs.